(3TQM GdSQGLjIs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s; (3SQGL GdOjf CHh WGgQ eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj,J (B598 (3g` ? s
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde GdLeghQ Ydi Cf GdQShd CNU ef GdfHi hjOd Ydjg XGgQ bhdg JYGdi (B: (3heG CQSdfG ef bHdc ef QShd hdG fHi s
(3BNQgG (B:s
(3dCf cdkG efgeG dGjQK ef UGMHg aChQK UGMHg efg , abO ELJeY ddCe YTQhf hdHfJ cd hGMO efgeG JSYhf hGdehdi YTQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdESdGejs